Assumptions for the concept of independent living of people with disabilities in the European Network on Independent Living - Greniuk, Angelika (Understanding Disability: Issues, Research, Reflections, 2021)
The Independent Living Movement is a global social movement whose idea and philosophy were defined in the United States in the 1970s. There were grassroots initiatives of people with disabilities in Europe, referring to independent living, but there was no connection between them. It was only later that activists with disabilities, coming back to the roots of the independent living movement, have contributed to innovative changes that have responded to the needs of people with disabilities in their countries. Over 30 years ago, these same activists created the European Network on Independent Living (ENIL), which is part of the Independent Living Movement. The article presents the source and emergence of the Independent Living Movement in the United States, the adaptation of the movement in Europe, the creation of the ENIL Network, and the philosophy of independent living with its most important elements.